Pylorus preservation pancreatectomy or not - Klaiber, Ulla; Probst, Pascal; Büchler, Markus W.; Hackert, Thilo (Translational gastroenterology and hepatology, 2017)
Pancreaticoduodenectomy (PD) is the treatment of choice for various benign and malignant tumors of the pancreatic head or the periampullary region, and the only hope for cure in patients with cancer at this side. While it has been associated with high morbidity and mortality rates in the last century, its centralization in specialized institutions together with refinements in the operative technique and better management of postoperative complications have made PD a standardized, safe procedure. Besides the classic Whipple procedure including distal gastrectomy, two variations of PD with or without pylorus resection, but preservation of the entire stomach in either procedure exist today. Pylorus-preserving PD has gained wide acceptance as standard procedure and is being performed by an increasing number of pancreatic surgeons. After its oncological adequacy was questioned initially, pylorus-preserving PD was shown to be equivalent to the classic Whipple procedure regarding tumor recurrence and long-term survival. Moreover, operation time and blood loss were shown to be reduced in the pylorus-preserving procedure and benefits in nutritional status and quality of life were observed. However, preservation of the pylorus has been suggested to result in an increased incidence of postoperative delayed gastric emptying (DGE). In this context, pylorus-resecting PD has become popular especially in Japan with the aim to prevent DGE by removal of the pylorus but preservation of the stomach. In contrast to positive results from early studies, latest high-quality randomized controlled trial (RCT) data show that pylorus resection does not reduce DGE compared to the pylorus-preserving operation. Non-superiority of pylorus resection was also confirmed in current meta-analysis on this topic. This article summarizes the existing evidence on PD with or without pylorus preservation and derives recommendations for daily practice.
Published: 04 December 2017
Gesehen am 22.10.2018